The Duchess effect : a novel - Livesay, Tracey (American royalty, 2023)
Taking their relationship public, American rapper Danielle "Duchess" Nelson and brilliant reclusive royal Prince Jameson learn that their popularity comes with a price when people try to take advantage of their fame, especially when his family is embroiled in yet another scandal.